2019
DOI: 10.1002/smll.201904145
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Philic Separation Membrane: Deep Eutectic Solvent Filled Graphene Oxide Nanoslits

Abstract: CO2 capture and sequestration is an energy‐intensive industry to deal with the global greenhouse effect. Membrane separation is considered a cost‐effective method to mitigate the emission of CO2. Though good separation performance and stability have been reported, supported ionic liquid membranes are still not widely applied for CO2 separation due to the high cost. As a novel analogous solvent to ionic liquid, deep eutectic solvent retains the excellent merits of ionic liquid and is cheap with facile preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 66 publications
1
37
0
Order By: Relevance
“…Vacuum filtration coupled with impregnation was used for the fabrication of graphene oxide-ChCl-ethylene glycol DESbased composite SLMs (42). Lin (42) optimized the fabrication duration between 10 s and 2 h over the graphene oxide-ChClethylene glycol DES-based composite SLM.…”
Section: Fabrication Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vacuum filtration coupled with impregnation was used for the fabrication of graphene oxide-ChCl-ethylene glycol DESbased composite SLMs (42). Lin (42) optimized the fabrication duration between 10 s and 2 h over the graphene oxide-ChClethylene glycol DES-based composite SLM.…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…Vacuum filtration coupled with impregnation was used for the fabrication of graphene oxide-ChCl-ethylene glycol DESbased composite SLMs (42). Lin (42) optimized the fabrication duration between 10 s and 2 h over the graphene oxide-ChClethylene glycol DES-based composite SLM. Although, this method produced SLMs with uniform morphology, its high capital cost and maintenance problems with frequent leakage limit its employment.…”
Section: Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various nanomaterials, graphene oxide (GO) nanosheets received great attention due to their high flexibility, good mechanical strength, and easy processability. Lin et al ( 2019 ) confined a deep eutectic solvent that is selective to CO 2 , similar to ILs, into GO nanoslits as a highly CO 2 -philic GO-SILM. The group reported a structural change in the liquid that better promotes CO 2 transport, even though the liquid is not reactive with CO 2 .…”
Section: Developments Toward the Il-based Ftmsmentioning
confidence: 99%
“…Furthermore, it is possible to fabricate various membranes for different applications owing to the diverse monomers available and the polymers that are synthesized from them with different structural properties. In recent years, membrane technology for CO 2 separation has attracted significant research interest [ 9 , 10 , 11 , 12 ]. In particular, studies have reported on CO 2 /N 2 , CO 2 /CH 4 , and CO 2 /H 2 separation techniques [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%